High-voltage positive electrode material and preparation method thereof, positive plate and sodium ion battery
By heat treatment of a variety of coating agents on the O3-phase layered oxide matrix material, a uniform composite material is formed, which solves the problem of irreversible phase change of sodium ion batteries at high voltage, and significantly improves the circulation performance and stability.
Patent Information
- Application Number
- CN202411258406.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing sodium ion battery layered positive electrode materials have problems such as irreversible phase change, lattice oxygen loss, volume expansion at high voltage, resulting in particle rupture, oxygen release and electrolyte corrosion, affecting battery capacity and cycling performance.
The O3-phase layered oxide matrix material is heat treated with a variety of coating agents to form a uniformly distributed composite material, improve the electron transfer rate and cycle stability, separate the contact between the electrolyte and the matrix material, and prevent corrosion.
Reversible phase transition and excellent cycling performance at high voltage (≥4.3V), improve the rate performance and structural stability of the material, prevent the dissolution of the transition metal, and extend the battery life.
Smart Images

Figure CN119133402A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a high-voltage positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] At present, under the guidance of the "dual carbon" goals, new energy installed capacity continues to grow rapidly, and a new power system with new energy as the main body is being accelerated. Among them, sodium-ion batteries have huge reserves and low prices, which can reduce the cost of large-scale energy storage and are an ideal choice for the next generation of large-scale power sources.
[0003] However, most of the research on layered cathode materials for sodium-ion batteries is carried out around the range of 2 to 4V. This is because when the charging cut-off voltage is higher than 4V, an irreversible phase change of the cathode material will occur, and a series of problems such as easy loss of lattice oxygen, particle breakage caused by volume expansion, oxygen release caused by energy level overlap, easy corrosion and damage by electrolyte, and easy dissolution of active elements will occur, further leading to practical problems such as battery capacity attenuation and poor cycle performance, which are difficult to meet actual application scenarios. Therefore, it is of great significance to vigorously develop and design new sodium-ion battery cathode materials with high energy density and power density, long life, safety and low cost.
[0004] According to the mechanism of capacity attenuation of high-voltage positive electrode materials, the materials can be modified in a targeted manner to improve the material's cycle stability. Generally speaking, phase change is an intrinsic problem of the material, and the material structure needs to be designed and developed, such as through doping and other methods. The stability of the interface of the positive electrode material under high voltage is an important factor affecting the electrochemical properties of the material, which can generally be improved by coating and modifying the surface of the material. However, in the prior art, the coating of a single or more elements is mostly performed by first grinding or mechanically mixing with the substrate, and then sintering to obtain a modified product. However, when the number of coated elements exceeds two or more, it is easy to cause uneven coating of the elements and local segregation of the elements.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a high voltage positive electrode material, which has a reversible phase change at a high voltage greater than 4V, can operate at a high voltage, and has excellent cycle performance.
[0007] The second purpose of the present invention is to provide a method for preparing a high-voltage positive electrode material. When more than two coating agents are used, the present invention pre-wet-mixes the coating agents to obtain a composite material with uniformly distributed elements, and then coats the composite material with an O3 phase layered oxide matrix material through heat treatment. This allows each coating agent to be evenly distributed on the surface of the matrix material, thereby increasing the electron transfer rate of the material, increasing the electronic conductivity coefficient, and increasing the rate performance and cycle stability of the high-voltage positive electrode material. It can also effectively isolate the O3 phase layered oxide matrix material from direct contact with the electrolyte, thereby avoiding corrosion of the electrolyte that causes transition metal dissolution and causes material failure.
[0008] The third object of the present invention is to provide a positive electrode sheet having high capacity and good cycle performance.
[0009] A fourth object of the present invention is to provide a sodium ion battery having high capacity and excellent cycle performance.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The present invention first provides a high-voltage positive electrode material, comprising an O3 phase layered oxide matrix material and a coating layer coated on the surface of the O3 phase layered oxide matrix material.
[0012] Wherein, the chemical formula of the O3 phase layered oxide matrix material is Na a Ni x A y Mn p G q O 2 , wherein A includes +2 and / or +3 valence metal elements, G includes +4 valence metal elements, 0.8≤a≤1.05, 0.3≤x≤0.5, 0≤y≤0.2, 0.3≤p≤0.5, 0≤q≤0.2, x+y+p+q=1, 2(x+y)+4(p+q)≤3, and y and q are not 0 at the same time.
[0013] The modifying element in the coating layer includes at least one of Al, B, Ca, Co, Ce, La, Mg, Mo, Nb, Sr, Sn, W, Y, Zr, Zn, Bi and Ti.
[0014] Furthermore, the +2 valence metal element in A includes at least one of Ca, Zn, Cu and Mg.
[0015] Furthermore, the +3 valence metal element in A includes at least one of Fe and Co.
[0016] Furthermore, the G includes at least one of Ti, Ce, Zr and Mo.
[0017] Furthermore, the mass of the coating layer accounts for 0.3% to 10% of the mass of the O3 phase layered oxide matrix material.
[0018] Furthermore, the coating layer includes an oxide of a modifying element.
[0019] The present invention further provides a method for preparing the high voltage positive electrode material, comprising the following steps:
[0020] (a) mixing a mixed aqueous solution containing a nickel source, a manganese source, a dispersant and an additive with a precipitant solution and subjecting them to a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor; or mixing a mixed aqueous solution containing a nickel source, a manganese source and a dispersant, an organic solution or an acid solution containing an additive, and a precipitant solution, and subjecting them to a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor; or mixing a mixed aqueous solution containing a nickel source, a manganese source, a dispersant and an additive, an organic solution or an acid solution containing an additive, and a precipitant solution, and subjecting them to a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor; wherein the additive comprises an A-containing compound and / or a G-containing compound, A comprises a +2 and / or +3 valence metal element, and G comprises a +4 valence metal element; optionally, calcining the hydroxide precursor and / or the carbonate precursor to obtain an oxide precursor.
[0021] (b) mixing at least one of the hydroxide precursor, the carbonate precursor and the oxide precursor with a sodium source, and then sintering to obtain an O3 phase layered oxide matrix material.
[0022] (c) When one coating agent is used, the O3 phase layered oxide matrix material is mixed with the coating agent and then subjected to heat treatment to obtain the high voltage positive electrode material; or, when at least two coating agents are used, each of the coating agents, dispersing additives and water are first mixed and ultrasonicated, and then the solid-liquid separation and drying are performed to obtain a composite material, and then the composite material is mixed with the O3 phase layered oxide matrix material and subjected to heat treatment to obtain the high voltage positive electrode material; wherein the coating agent includes a compound containing a modifying element, and the modifying element includes at least one of Al, B, Ca, Co, Ce, La, Mg, Mo, Nb, Sr, Sn, W, Y, Zr, Zn, Bi and Ti.
[0023] Furthermore, in step (a), the dispersant includes at least one of soluble starch, polyvinyl pyrrolidone, sodium dodecyl sulfate and polyethylene glycol.
[0024] Furthermore, in step (a), the organic solvent in the organic solution containing the additive comprises at least one of ethanol, dichloromethane and anhydrous tetrahydrofuran.
[0025] Furthermore, in step (a), the A-containing compound includes at least one of A-containing nitrates, A-containing sulfates, A-containing chlorides and A-containing acetates.
[0026] Furthermore, in step (a), the G-containing compound includes at least one of a G-containing nitrate, a G-containing sulfate, a G-containing chloride and a G-containing acetate.
[0027] Furthermore, in step (a), the +2 valence metal element in A includes at least one of Ca, Zn, Cu and Mg, and the +3 valence metal element in A includes at least one of Fe and Co.
[0028] Furthermore, in step (a), the G includes at least one of Ti, Ce, Zr and Mo.
[0029] Furthermore, in step (a), the precipitant solution comprises at least one of a sodium carbonate solution, a sodium hydroxide solution and an ammonia solution.
[0030] Furthermore, in step (a), the pH of the coprecipitation reaction is 7-13.
[0031] Furthermore, in step (a), the calcination temperature is 400-700° C., and the holding time is 6-12 hours.
[0032] Furthermore, in step (a), the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
[0033] Furthermore, in step (b), the sodium source includes sodium carbonate and / or sodium hydroxide.
[0034] Furthermore, in step (b), the sintering temperature is 850-1050° C., and the holding time is 12-24 hours.
[0035] Furthermore, in step (b), the sintering includes: firstly keeping the temperature at 400-600°C for 3-6 hours, and then keeping the temperature at 850-1050°C for 14-18 hours.
[0036] Furthermore, in step (b), the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0037] Furthermore, in step (c), the total mass of each of the coating agents accounts for 0.3% to 10% of the mass of the O3 phase layered oxide matrix material.
[0038] Furthermore, in step (c), the dispersing additive includes at least one of sodium polyacrylate, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium lauryl sulfate, polyvinyl alcohol and polyethylene oxide.
[0039] Furthermore, in step (c), the ultrasonication time is 30 to 60 minutes.
[0040] Furthermore, in step (c), the heat treatment temperature is 500-950° C., and the insulation time is 10-16 hours.
[0041] Furthermore, in step (c), the atmosphere of the heat treatment includes air atmosphere and / or oxygen atmosphere.
[0042] Furthermore, in step (c), the compound containing the modifying element includes at least one of carbonates, bicarbonates, nitrates, acetates, oxalates, hydroxides, sulfates, chlorides and oxides containing the modifying element.
[0043] The present invention further provides a positive electrode sheet, comprising the high-voltage positive electrode material.
[0044] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The high-voltage positive electrode material provided by the present invention has a reversible phase change under high voltage, can operate under high voltage (≥4.3V), and has excellent cycle performance.
[0047] (2) The high-voltage positive electrode material provided by the present invention improves the stability of the interface between the material and the electrolyte: the coating material can effectively isolate the direct contact between the base material and the electrolyte, enhance the structural stability of the positive electrode material, prevent the dissolution of the transition metal, and inhibit side reactions with the electrolyte.
[0048] (3) The high-voltage positive electrode material provided by the present invention improves the electrical conductivity of the material: the coating material is evenly distributed on the surface of the base material, and a large number of local heterojunction structures of the base material and the coating material are obtained, which can reduce the battery polarization and the interface resistance of the positive electrode material / electrolyte, and can enhance the surface Na + conduction and improve rate performance.
[0049] (4) The preparation method of the high-voltage positive electrode material provided by the present invention, when at least two coating agents are used, the coating materials are pre-wet mixed to obtain a composite coating material with uniform element distribution, and then the composite coating material is composited with the base material by heat treatment. The composite coating material is uniformly distributed on the surface of the base material, and a large number of local heterojunction structures of the base material and the coating material are obtained, which enhances the electron transfer rate of the material and improves the electronic conductivity coefficient; on the other hand, the heterostructure is reasonably constructed, and the multi-phase synergistic effect is achieved by relying on the various heterojunction structures formed by the (multi-element) coating material on the surface of the base material, showing various excellent characteristics of the two-phase material, achieving material performance that is difficult to achieve with a single-phase material, and significantly improving the rate performance and cycle stability of the material; furthermore, the coating material can effectively separate the base material from direct contact with the electrolyte, avoiding the material failure caused by the dissolution of transition metals due to the corrosion of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0051] Figure 1 A schematic diagram of a coprecipitation reaction in a three-necked flask provided by the present invention. DETAILED DESCRIPTION
[0052] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0053] In a first aspect, the present invention provides a high voltage positive electrode material for a sodium ion battery, comprising an O3 phase layered oxide matrix material, and a coating layer coated on the surface of the O3 phase layered oxide matrix material.
[0054] The chemical formula of the O3 phase layered oxide matrix material is Na a Ni x A y Mnp G q O 2 , wherein A includes +2 valence metal elements and / or +3 valence metal elements, G includes +4 valence metal elements, 0.8≤a≤1.05, 0.3≤x≤0.5, 0≤y≤0.2, 0.3≤p≤0.5, 0≤q≤0.2, x+y+p+q=1, 2(x+y)+4(p+q)≤3, and y and q are not 0 at the same time. A and G can work together with transition metals Ni and Mn to regulate the crystal structure.
[0055] The above chemical formula Na a Ni x A y Mn p G q O 2 In the formula, a includes but is not limited to any one of 0.8, 0.83, 0.85, 0.88, 0.9, 0.92, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05, or any range between two of them; x includes but is not limited to any one of 0.3, 0.33, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, 0.5, or any range between two of them; y includes but is not limited to 0, 0.001, 0.005, 0.01, 0.02, 0.03, 0.0 5, 0.08, 0.1, 0.12, 0.13, 0.15, 0.18, 0.2, or a range between any two of them; p includes but is not limited to any one of 0.3, 0.33, 0.35, 0.38, 0.4, 0.43, 0.45, 0.48, 0.5, or a range between any two of them; q includes but is not limited to any one of 0, 0.001, 0.005, 0.01, 0.02, 0.03, 0.05, 0.08, 0.1, 0.12, 0.13, 0.15, 0.18, 0.2, or a range between any two of them.
[0056] The modifying elements in the coating layer include at least one of Al, B, Ca, Co, Ce, La, Mg, Mo, Nb, Sr, Sn, W, Y, Zr, Zn, Bi and Ti, preferably at least two, for example, two, three, four, five, six or more.
[0057] The high voltage positive electrode material provided by the present invention comprises an O3 phase single crystal layered oxide matrix material with a specific chemical composition, which has a reversible phase transition at a high voltage greater than 4V, can operate at a high voltage (≥4.3V) and has excellent cycle performance. This is because, in Na +During the process of intercalation and deintercalation (charge and discharge), the transition between the O phase and the P phase occurs, which often leads to a large change in the unit cell volume. The large lattice internal stress is the cause of the formation and expansion of microcracks, which has an adverse effect on the stability of the layered structure and the diffusion of sodium ions, further leading to the collapse of the cycle structure and the decline of electrochemical performance. + During the electrochemical process of embedding and de-embedding, the change in the lattice parameter c-axis is significantly reduced, that is, the volume phase change is relatively small, that is, there is a reversible phase change under high voltage, so it can maintain structural stability during long-term cycling.
[0058] In some specific embodiments, the +2 valence metal element in A includes at least one of Ca, Zn, Cu and Mg elements, for example, two, three or four.
[0059] In some specific embodiments, the +3 valence metal element in A includes at least one of Fe and Co elements, or both.
[0060] In some specific embodiments, the G includes at least one of Ti, Ce, Zr and Mo, for example, two, three, four or more.
[0061] In some specific embodiments, the mass of the coating layer accounts for 0.3% to 10% of the mass of the O3-phase layered oxide matrix material, including but not limited to any point value of 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any range value between two of them.
[0062] In some specific embodiments, the coating layer is an oxide containing at least one modifying element.
[0063] In a second aspect, the present invention provides a method for preparing the high voltage positive electrode material, comprising the following steps:
[0064] (a) Preparing the precursor by co-precipitation method:
[0065] A mixed aqueous solution containing a nickel source, a manganese source, a dispersant and an additive is mixed with a precipitant solution and subjected to a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor.
[0066] Alternatively, a mixed aqueous solution containing a nickel source, a manganese source and a dispersant, an organic solution or an acid solution containing an additive, and a precipitant solution are mixed and subjected to a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor. The organic solution containing an additive refers to a mixed solution of an additive and an organic solvent. The acid solution containing an additive refers to a mixed solution of an additive and an acid. The acid may include any acid commonly used in the art, such as hydrochloric acid, but is not limited thereto.
[0067] Alternatively, a mixed aqueous solution containing a nickel source, a manganese source, a dispersant and an additive, an organic solution or an acid solution containing an additive, and a precipitant solution are mixed and subjected to a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor.
[0068] The above-mentioned additives refer to dopants, and the additives specifically include A-containing compounds and / or G-containing compounds, A includes +2 valence metal elements and / or +3 valence metal elements, and G includes +4 valence metal elements.
[0069] Optionally, the hydroxide precursor and / or the carbonate precursor is calcined to obtain an oxide precursor. Here, "optionally" means optional or not optional.
[0070] In some specific embodiments, when the additive is easily hydrolyzed, the additive can be dissolved in an organic solvent or acid to obtain an organic solution or acid solution containing the additive, and the coprecipitation reaction can be carried out. This can avoid the problem of uneven precipitation caused by the easily hydrolyzed element being precipitated separately in an uncontrolled pH range, thereby avoiding the element segregation phenomenon. Among them, the easily hydrolyzed additive includes an additive containing Ti.
[0071] In some specific embodiments, a mixed aqueous solution containing a nickel source, a manganese source and a dispersant, an organic solution or an acid solution containing an additive, and a precipitant solution are mixed and subjected to a coprecipitation reaction, and the organic solution or the acid solution containing the additive is first added dropwise to the mixed aqueous solution containing the nickel source, the manganese source and the dispersant using a peristaltic pump to obtain a mixed solution. Then, the precipitant solution is added dropwise to the mixed solution using a peristaltic pump to perform a coprecipitation reaction.
[0072] In some specific implementations, such as Figure 1 As shown, the coprecipitation reaction is carried out in a three-necked flask, with a mixed aqueous solution containing a nickel source, a manganese source and a dispersant as liquid M, an organic solution or an acid solution containing an additive as liquid N, and a precipitant solution as liquid L, and liquid M, liquid N and liquid L are added respectively, mixed and reacted. Preferably, stirring is continued during the coprecipitation reaction.
[0073] In some specific embodiments, after the coprecipitation reaction is completed, the obtained precipitate is washed and dried.
[0074] (b) mixing at least one of the hydroxide precursor, the carbonate precursor and the oxide precursor with a sodium source, and then sintering to obtain an O3 phase layered oxide matrix material.
[0075] In some specific embodiments, in step (b), the mixing is performed using a high-speed mixer.
[0076] In some specific implementations, in step (b), the sintering further includes the steps of jet milling and screening.
[0077] (c) Coating modification:
[0078] When a coating agent is used, the O3 phase layered oxide matrix material is mixed with the coating agent and then heat treated. After cooling, the mixture is crushed and sieved by a jet mill to obtain the high voltage positive electrode material.
[0079] Alternatively, when at least two coating agents are used, the coating agents, dispersing additives and water are first mixed and ultrasonicated, then solid-liquid separation and drying are performed to obtain a composite material, and then the composite material is mixed with the O3 phase layered oxide matrix material and heat treated, and after cooling, the composite material is crushed and sieved by a jet mill to obtain the high voltage positive electrode material. This can ensure uniform coating and improve the cycle stability of the obtained positive electrode material.
[0080] The above-mentioned coating agent includes a compound containing a modifying element, and the modifying element includes at least one of Al, B, Ca, Co, Ce, La, Mg, Mo, Nb, Sr, Sn, W, Y, Zr, Zn, Bi and Ti.
[0081] In some specific embodiments, the heat treatment is performed in an atmosphere furnace.
[0082] The present invention obtains a precursor material with uniform particle size distribution by regulating the precursor coprecipitation process, and enables a reversible phase change under high voltage by regulating the components of the O3 phase layered oxide matrix material and its preparation process.
[0083] At the same time, the present invention can further improve the cycle stability of the positive electrode material by surface coating and modification of the O3 phase layered oxide matrix material. Specifically, when at least two coating agents are used, the present invention obtains a composite coating material with uniform element distribution by pre-wet mixing the coating material, and then composites it with the matrix material by heat treatment. The composite coating material is evenly distributed on the surface of the matrix material to obtain countless local heterojunction structures of the matrix material and the coating material, which enhances the electron transfer rate of the material and improves the electronic conductivity coefficient; on the other hand, the heterostructure is reasonably constructed, and the multi-phase synergistic effect is achieved by relying on the various heterojunction structures formed by the (multi-element) coating material on the surface of the matrix material, showing various excellent properties of the two-phase material, achieving material performance that is difficult to achieve with a single-phase material, and significantly improving the rate performance and cycle stability of the material; furthermore, the coating material can effectively separate the direct contact between the matrix material and the electrolyte, avoiding the material failure caused by the dissolution of transition metals caused by the corrosion of the electrolyte.
[0084] In some specific embodiments, in step (a), the dispersant includes at least one of soluble starch, polyvinyl pyrrolidone (PVP), sodium dodecyl sulfate (SDS) and polyethylene glycol (PEG-6000). The addition of the dispersant can improve the stability of the suspension, so that the particles are evenly distributed in the liquid and are not easy to settle, thereby ensuring the uniformity and controllability of the coprecipitation process; on the other hand, by selecting different types of dispersants and dosages, the growth rate and morphology of the particles can be affected, thereby regulating the particle size and distribution of the final precursor.
[0085] In some specific embodiments, in step (a), the organic solvent in the organic solution containing the additive includes at least one of ethanol, dichloromethane and anhydrous tetrahydrofuran (THF), and two, three, four or more of them can be selected.
[0086] In some specific embodiments, in step (a), the A-containing compound includes at least one of A-containing nitrates, A-containing sulfates, A-containing chlorides and A-containing acetates, and two, three, four or more of them can be selected.
[0087] In some specific embodiments, in step (a), the G-containing compound includes at least one of a G-containing nitrate, a G-containing sulfate, a G-containing chloride and a G-containing acetate, and two, three, four or more of them can be selected.
[0088] In some specific embodiments, in step (a), the +2 valence metal element in A includes at least one of Ca, Zn, Cu and Mg, and the +3 valence metal element in A includes at least one of Fe and Co.
[0089] In some specific implementations, in step (a), G includes at least one of Ti, Ce, Zr and Mo, and two, three, four or more of them can be selected.
[0090] In some specific embodiments, in step (a), the precipitant solution includes at least one of a sodium carbonate solution, a sodium hydroxide solution and an ammonia solution, and two or three thereof may also be selected.
[0091] In some specific embodiments, in step (a), the pH of the coprecipitation reaction is 7 to 13, including but not limited to any one of 7, 8, 9, 10, 11, 12, 13 or a range between any two of them.
[0092] Preferably, during the coprecipitation reaction to obtain the carbonate precursor, the pH value of the reaction system is controlled between 7 and 10. During the coprecipitation reaction to obtain the hydroxide precursor, the pH value of the reaction system is controlled between 10 and 13. The pH controlled varies depending on the precipitant. By adjusting the pH value, the morphology of the primary grains and secondary particles can be controlled to obtain a precursor with uniform particle size distribution.
[0093] In some specific embodiments, in step (a), the calcination temperature is 400-700°C, including but not limited to any one of 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, and 700°C, or a range between any two of them; the calcination holding time is 6-12h, including but not limited to any one of 6h, 7h, 8h, 9h, 10h, 11h, and 12h, or a range between any two of them.
[0094] In some specific embodiments, in step (a), the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
[0095] In some specific embodiments, in step (b), the sodium source includes sodium carbonate and / or sodium hydroxide.
[0096] In some specific embodiments, in step (b), the sintering temperature is 850-1050°C, including but not limited to any one of 850°C, 900°C, 950°C, 1000°C, 1050°C or a range between any two of them; the sintering holding time is 12-24h, including but not limited to any one of 12h, 14h, 18h, 20h, 22h, 24h or a range between any two of them.
[0097] In some specific embodiments, in step (b), the sintering includes: first keeping warm at 400-600°C (including but not limited to any one of 400°C, 450°C, 500°C, 550°C, 600°C or any range between two of them) for 3-6h (including but not limited to any one of 3h, 4h, 5h, 6h or any range between two of them), and then keeping warm at 850-1050°C (including but not limited to any one of 850°C, 900°C, 950°C, 1000°C, 1050°C or any range between two of them) for 14-18h (including but not limited to any one of 14h, 15h, 16h, 18h or any range between two of them).
[0098] In some specific embodiments, in step (b), the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0099] In some specific embodiments, in step (c), the total mass of each of the coating agents accounts for 0.3% to 10% of the mass of the O3 phase layered oxide matrix material; including but not limited to any point value of 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range value between any two of them.
[0100] In some specific embodiments, in step (c), the dispersing additive includes at least one of sodium polyacrylate (PAA), polyvinyl pyrrolidone (PVP), carboxymethyl cellulose (CMC), sodium dodecyl sulfate (SDS), polyvinyl alcohol (PVA) and polyethylene oxide (PEO), for example, two, three or more.
[0101] In some specific embodiments, in step (c), the ultrasonic time is 30 to 60 minutes, including but not limited to any one of 30 minutes, 40 minutes, 50 minutes, and 60 minutes, or a range between any two of them.
[0102] In some specific embodiments, in step (c), the drying temperature is 80-120°C, including but not limited to any one of 80°C, 90°C, 100°C, 120°C or a range between any two of them.
[0103] In some specific embodiments, in step (c), the heat treatment temperature is 500-950°C, including but not limited to any one of 500°C, 600°C, 700°C, 800°C, 900°C, 950°C or a range between any two of them; the holding time is 10-16h, including but not limited to any one of 10h, 12h, 14h, 16h or a range between any two of them.
[0104] In some specific embodiments, in step (c), the atmosphere of the heat treatment includes air atmosphere and / or oxygen atmosphere.
[0105] In some specific embodiments, in step (c), the compound containing the modifying element includes at least one of carbonates, bicarbonates, nitrates, acetates, oxalates, hydroxides, sulfates, chlorides and oxides containing the modifying element, for example, two, three, four or more.
[0106] In a third aspect, the present invention provides a positive electrode sheet comprising the high voltage positive electrode material.
[0107] The positive electrode sheet has high charge and discharge capacity and good cycle performance.
[0108] Optionally, the positive electrode sheet further includes a binder and a conductive agent, which is not limited in the present invention.
[0109] In a fourth aspect, the present invention provides a sodium ion battery comprising the positive electrode sheet.
[0110] The sodium ion battery has the advantages of high capacity, good rate performance, and excellent cycle performance.
[0111] Optionally, the sodium ion battery further comprises a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention.
[0112] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0113] Example 1
[0114] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.9 Cu 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 , and a coating layer ZrO coated on the surface of the O3 phase layered oxide matrix material 2 , wherein the mass of the coating layer is 0.5% of the mass of the O3 phase layered oxide matrix material, and the preparation method of the high voltage positive electrode material comprises the following steps:
[0115] (1) Preparation of O3 phase layered oxide matrix material:
[0116] NiSO 4 6H 2 O、CuSO 4 6H 2 O、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio (Ni:Cu:Mn molar ratio = 4:1:4), and the solvent was pure water to obtain a total molar concentration of metal elements of 2 mol·L -1 The salt solution was added with dispersant SDS, which was recorded as M solution. The M solution was transferred to a three-necked flask in a 50°C water bath and stirred continuously. 4 , disperse it in THF, record it as liquid N. Use a peristaltic pump to add liquid N dropwise to liquid M. After the addition of liquid N is completed, use a peristaltic pump to add a precipitant with a molar concentration of 4 mol·L dropwise. -1 Na 2 CO 3 The solution was prepared by centrifuging the solution several times to remove the acid ions and complex residues until the pH of the solution was 7. The solution was dried by blasting at 120°C to obtain a carbonate precursor with a median particle size of 4 μm. The carbonate precursor was placed in an atmosphere furnace, compressed air was introduced, and calcined at 550°C for 6 hours to obtain an oxide precursor Cu. 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 .
[0117] The above oxide precursors and Na 2 CO 3 , and mix them using a high-speed mixer. The mixture is then sintered in an atmosphere furnace and compressed air is introduced. The heating rate is 3°C / min, and the mixture is kept at 950°C for 15 hours. After it is naturally cooled, the obtained block material is crushed and sieved through a jet mill to obtain an O3 phase layered oxide matrix material.
[0118] (2) Coating modification:
[0119] According to the above coating ratio, the above O3 phase layered oxide matrix material and ZrO 2 , use a high-speed mixer to mix evenly, put it into a sagger, sinter (i.e., heat treat) it at 850°C in a compressed air atmosphere for 12 hours, and then cool it naturally to room temperature to obtain a high-voltage positive electrode material.
[0120] Example 2
[0121] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na0.9 Cu 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 , and a coating layer B coated on the surface of the O3 phase layered oxide matrix material 2 O 3 , wherein the mass of the coating layer is 1% of the mass of the O3 phase layered oxide matrix material, and the preparation method of the high voltage positive electrode material comprises the following steps:
[0122] (1) Preparation of O3 phase layered oxide matrix material:
[0123] NiSO 4 6H 2 O、CuSO 4 6H 2 O、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 The salt solution was added with dispersant PEG-6000, which was recorded as M solution. The solution was transferred to a three-necked flask in a 40°C water bath and stirred continuously. 4 , and dissolve it in dichloromethane, recorded as liquid N. Use a peristaltic pump to add liquid N dropwise to liquid M. After the addition of liquid N is completed, use a peristaltic pump to add precipitant solution 4 mol·L dropwise to it. -1 The NaOH solution was used to control the pH of the precipitation process to be between 12 and 13. After the precipitation was complete, pure water was used for multiple centrifugal washing to remove the acid ions and complex residues until the pH of the washing solution was 7, and then the solution was dried at 120°C with air blast to obtain a hydroxide precursor Cu with a median particle size of 3 μm. 0.1 Ni 0.4 Mn 0.4 Ti 0.1 (OH) 2 .
[0124] According to the stoichiometric ratio, the above hydroxide precursor and Na 2 CO 3 The mixture is mixed by a high-speed mixer; the mixture is sintered in an atmosphere furnace and compressed air is introduced at a heating rate of 3°C / min, and the mixture is kept at 500°C for 3 hours and at 980°C for 14 hours. The obtained product is air flow-pulverized and sieved to obtain an O3 phase layered oxide matrix material.
[0125] (2) Coating modification:
[0126] According to the above coating ratio, weigh the above O3 phase layered oxide matrix material and B 2 O 3 , use a high-speed mixer to mix evenly, put it into a sagger, sinter it at 850℃ for 12h in a compressed air atmosphere, and then cool it naturally to room temperature to obtain a high-voltage positive electrode material.
[0127] Example 3
[0128] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.9 Cu 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 , and a coating layer CoO coated on the surface of the O3 phase layered oxide matrix material, wherein the mass of the coating layer is 0.8% of the mass of the O3 phase layered oxide matrix material, and the preparation method of the high voltage positive electrode material comprises the following steps:
[0129] (1) Preparation of O3 phase layered oxide matrix material:
[0130] NiSO 4 6H 2 O、CuSO 4 6H 2 O、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 Then add the dispersant PVP to the salt solution, record it as M solution, transfer it to a three-necked flask in a 60℃ water bath and stir it continuously. 4 , and dissolve it in ethanol, recorded as liquid N. Use a peristaltic pump to add liquid N dropwise to liquid M. After the addition of liquid N is completed, use a peristaltic pump to add 4 mol·L -1 The precipitation agent ammonia solution is used to control the pH of the precipitation process between 12 and 13. After the precipitation is complete, pure water is used for multiple centrifugal washing to remove acid ions and complex residues until the pH of the washing solution is 7, and then the solution is dried by air blast at 120°C to obtain a hydroxide precursor with a median particle size of 5 μm.
[0131] According to the stoichiometric ratio, the above hydroxide precursor and Na 2 CO 3The mixture is mixed by a high-speed mixer; the mixture is sintered in an atmosphere furnace and compressed air is introduced at a heating rate of 3°C / min, and the mixture is kept at 500°C for 3 hours and at 1000°C for 14 hours. The obtained product is air flow-pulverized and sieved to obtain an O3 phase layered oxide matrix material.
[0132] (2) Coating modification:
[0133] The above-mentioned O3 phase layered oxide matrix material and CoO were weighed respectively according to the above-mentioned coating ratio, mixed evenly using a high-speed mixer, and put into a sagger, sintered at 850°C for 12 hours in a compressed air atmosphere, and then naturally cooled to room temperature to obtain a high-voltage positive electrode material.
[0134] Example 4
[0135] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.9 Cu 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 , and a coating layer B-Zr composite oxide (i.e. B 2 O 3 and ZrO 2 The mass of the coating layer is 1.5% of the mass of the O3 phase layered oxide matrix material, wherein B 2 O 3 Mass fraction is 1%, ZrO 2 The mass fraction is 0.5%. The preparation method of the high voltage positive electrode material comprises the following steps:
[0136] (1) Preparation of O3 phase layered oxide matrix material:
[0137] NiSO 4 6H 2 O、CuSO 4 6H 2 O、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 Then add the dispersant SDS to the solution, which is called M solution, and transfer it to a three-necked flask in a 55°C water bath and stir continuously. 4 , and dispersed it in THF, recorded as liquid N. Use a peristaltic pump to add liquid N dropwise to liquid M. After the addition of liquid N is completed, use a peristaltic pump to add 4 mol·L -1 The precipitant Na2 CO 3 The solution was prepared by centrifuging the solution several times to remove the acid ions and complex residues until the pH of the washing solution reached 7. The carbonate precursor with a median particle size of 4 μm was obtained after air drying at 120°C. The carbonate precursor was placed in an atmosphere furnace, compressed air was introduced, and calcined at 550°C for 6 hours to obtain the precursor Cu 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 .
[0138] The above oxide precursors and Na 2 CO 3 , and mix them using a high-speed mixer. The mixture is then sintered in an atmosphere furnace and compressed air is introduced. The heating rate is 3°C / min, and the mixture is kept at 950°C for 15 hours. After it is naturally cooled, the obtained block material is crushed and sieved through a jet mill to obtain an O3 phase layered oxide matrix material.
[0139] (2) Coating modification:
[0140] According to the coating ratio, weigh B 2 O 3 and ZrO 2 Afterwards, it was dispersed in water, and a dispersing additive SDS was added. The resulting mixed solution was ultrasonically dispersed for 30 minutes, then filtered and washed, and placed in an 80° C. forced air drying oven for drying to obtain a composite material.
[0141] The O3 phase layered oxide matrix material and the composite material were weighed respectively according to the above coating ratio, mixed evenly using a high-speed mixer, and put into a sagger, sintered at 870° C. for 10 h in a compressed air atmosphere, and then naturally cooled to room temperature to obtain a high-voltage positive electrode material.
[0142] Example 5
[0143] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.9 Cu 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 , and the coating layer Co-B composite oxide (i.e. CoO and B) coated on the surface of the O3 phase layered oxide matrix material 2 O 3 The mass of the coating layer is 1.8% of the mass of the O3 phase layered oxide matrix material, wherein B 2 O3 The mass fraction of Cu is 1%, the mass fraction of CoO is 0.8%, and the preparation method of the high voltage positive electrode material comprises the following steps:
[0144] (1) Preparation of O3 phase layered oxide matrix material:
[0145] NiSO 4 6H 2 O、CuSO 4 6H 2 O、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 Then add the dispersant SDS to the solution, which is called M solution, and transfer it to a three-necked flask in a 45°C water bath and stir continuously. 4 , and dispersed it in THF, recorded as liquid N. Use a peristaltic pump to add liquid N dropwise to liquid M. After the addition of liquid N is completed, use a peristaltic pump to add 4 mol·L -1 The precipitant Na 2 CO 3 The solution was prepared by centrifugation to control the pH of the precipitation process between 7 and 10. After the precipitation was complete, pure water was used for multiple centrifugal washing to remove the acid ions and complex residues until the pH of the water washing solution was 7. After air drying at 120°C, a carbonate precursor with a median particle size of 4 μm was obtained. The carbonate precursor was placed in an atmosphere furnace, compressed air was introduced, and calcined at 550°C for 6 hours to obtain an oxide precursor Cu 0.1 Ni 0.4 Mn 0.4 Ti 0.1 O 2 .
[0146] The above oxide precursors and Na 2 CO 3 and mixed with a high-speed mixer, and then sintered in an atmosphere furnace, and introduced compressed air, with a heating rate of 3°C / min, and kept at 940°C for 15 hours. After it was naturally cooled, the obtained block material was crushed and sieved by a jet mill to obtain an O3 phase layered oxide matrix material.
[0147] (2) Coating modification:
[0148] According to the coating ratio, weigh B 2 O 3and CoO, dispersed them in water, and added dispersing additive CMC, the mixed solution was ultrasonically dispersed for 30 minutes, then filtered and washed, and placed in a 100° C. forced air drying oven for drying to obtain a composite material.
[0149] According to the above coating ratio, the above O3 phase layered oxide matrix material and the above composite material are weighed respectively, mixed evenly using a high-speed mixer, and put into a sagger, sintered at 830° C. for 12 hours in a compressed air atmosphere, and then naturally cooled to room temperature to obtain a high-voltage positive electrode material.
[0150] Example 6
[0151] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.95 Ni 0.4 Fe 0.2 Mn 0.4 O 2 , and the coating layer Al coated on the surface of the O3 phase layered oxide matrix material 2 O 3 , wherein the mass of the coating layer is 0.5% of the mass of the O3 phase layered oxide matrix material, and the preparation method of the high voltage positive electrode material comprises the following steps:
[0152] (1) Preparation of O3 phase layered oxide matrix material:
[0153] NiSO 4 6H 2 O, Fe(NO 3 ) 2 6H 2 O、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 Then add the dispersant SDS to the solution, which is called M solution. Transfer the solution to a three-necked flask in a 50°C water bath and stir it continuously. Use a peristaltic pump to add 4 mol·L -1 The precipitant Na 2 CO 3 The solution was prepared by centrifuging the solution several times to remove the acid ions and complex residues until the pH of the solution was 7. The carbonate precursor with a median particle size of 4 μm was obtained after air drying at 120°C. The carbonate precursor was placed in an atmosphere furnace, compressed air was introduced, and calcined at 600°C for 6 hours to obtain the oxide precursor Ni 0.4 Fe 0.2 Mn 0.4 O 2.
[0154] The above oxide precursors and Na 2 CO 3 The mixture is sintered in an atmosphere furnace and compressed air is introduced at a heating rate of 3°C / min and kept at 930°C for 18 hours. After it is naturally cooled, the obtained block material is crushed and sieved by a jet mill to obtain an O3 phase layered oxide matrix material.
[0155] (2) Coating modification:
[0156] According to the above coating ratio, weigh the above O3 phase layered oxide matrix material and Al 2 O 3 , use a high-speed mixer to mix evenly, put it into a sagger, sinter it at 900°C for 10 hours in a compressed air atmosphere, and then cool it naturally to room temperature to obtain a high-voltage positive electrode material.
[0157] Example 7
[0158] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.95 Ni 0.4 Fe 0.2 Mn 0.4 O 2 , and a coating layer CaO coated on the surface of the O3 phase layered oxide matrix material, wherein the mass of the coating layer is 3% of the mass of the O3 phase layered oxide matrix material, and the preparation method of the high voltage positive electrode material comprises the following steps:
[0159] (1) Preparation of O3 phase layered oxide matrix material:
[0160] Will Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 2 6H 2 O、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 Then add the dispersant PVP to the solution, which is called M solution. Transfer the solution to a three-necked flask in a 50°C water bath and stir continuously. Use a peristaltic pump to dropwise add 4 mol·L -1The precipitation agent NaOH solution was used to control the pH of the precipitation process between 12 and 13. After the precipitation was complete, pure water was used for multiple centrifugal washing to remove the acid ions and complex residues until the pH of the washing solution was 7, and then the solution was dried at 100°C with a forced air flow to obtain a hydroxide precursor Ni with a median particle size of 4 μm. 0.4 Fe 0.2 Mn 0.4 (OH) 2 .
[0161] Weigh the above hydroxide precursor and Na according to the stoichiometric ratio. 2 CO 3 The mixture is sintered in an atmosphere furnace and compressed air is introduced at a heating rate of 3°C / min. The mixture is kept at 500°C for 3h and at 970°C for 15h. After it is naturally cooled, the obtained block material is crushed and sieved by a jet mill to obtain an O3 phase layered oxide matrix material.
[0162] (2) Coating modification:
[0163] According to the above coating ratio, weigh the above O3 phase layered oxide matrix material and CaCO 3 (in terms of CaO), mix them evenly using a high-speed mixer, put them into a sagger, sinter them at 920°C for 10 hours in a compressed air atmosphere, and then naturally cool them to room temperature to obtain a high-voltage positive electrode material.
[0164] Example 8
[0165] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.95 Ni 0.4 Fe 0.2 Mn 0.4 O 2 , and a coating layer MgO coated on the surface of the O3 phase layered oxide matrix material, wherein the mass of the coating layer is 0.7% of the mass of the O3 phase layered oxide matrix material, and the preparation method of the high voltage positive electrode material comprises the following steps:
[0166] (1) Preparation of O3 phase layered oxide matrix material:
[0167] Ni(OCOCH 3 ) 2 ·4H 2 O, Fe(CO 2 CH 3 ) 2 , (CH 3 COO 2 Mn·4H 2O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 Add PEG-6000 to the salt solution, record it as M solution, transfer it to a three-necked flask in a 60℃ water bath and stir it continuously. Use a peristaltic pump to dropwise add 4 mol·L -1 The precipitation agent ammonia solution was used to control the pH of the precipitation process between 12 and 13. After the precipitation was complete, pure water was used for multiple centrifugal washing to remove the acid ions and complex residues until the pH of the washing solution was 7. The precursor was obtained after air drying at 110°C. The above precursor was placed in an atmosphere furnace, compressed air was introduced, and calcined at 600°C for 10 hours to obtain an oxide precursor Ni with a median particle size of 4μm. 0.4 Fe 0.2 Mn 0.4 O 1.5 .
[0168] The above oxide precursors and Na 2 CO 3 The mixture is sintered in an atmosphere furnace and compressed air is introduced at a heating rate of 3°C / min and kept at 970°C for 15 hours. After it is naturally cooled, the obtained block material is crushed and sieved by a jet mill to obtain an O3 phase layered oxide matrix material.
[0169] (2) Coating modification:
[0170] According to the above coating ratio, weigh the above O3 phase layered oxide matrix material and Mg(OH) 2 (in terms of MgO), mix them evenly using a high-speed mixer, put them into a sagger, sinter them at 870°C for 12 hours in a compressed air atmosphere, and then naturally cool them to room temperature to obtain a high-voltage positive electrode material.
[0171] Example 9
[0172] The high voltage positive electrode material provided in this embodiment includes an O3 phase layered oxide matrix material Na 0.95 Ni 0.4 Fe 0.2 Mn 0.4 O 2 , and a coating layer of Al-Ca-Mg composite oxide (i.e. Al 2 O 3 , CaO and MgO), wherein the mass of the coating layer is 4.2% of the mass of the O3 phase layered oxide matrix material, wherein Al 2 O 3The mass fractions of CaO, MgO are 0.5%, 3% and 0.7% respectively. The preparation method of the high voltage positive electrode material comprises the following steps:
[0173] NiSO 4 6H 2 O,Fe(NO 3 ) 2 6H 2 O,MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 Then add the dispersant SDS to the solution, which is called M solution. Transfer it to a three-necked flask in a 58°C water bath and stir it continuously. Use a peristaltic pump to dropwise add 4 mol·L -1 The precipitant Na 2 CO 3 The solution was prepared by centrifugation to control the pH of the precipitation process between 7 and 10. After the precipitation was complete, pure water was used for multiple centrifugal washing to remove the acid ions and complex residues until the pH of the water washing solution was 7. The carbonate precursor was obtained after air drying at 110°C. The above carbonate precursor was placed in an atmosphere furnace, compressed air was introduced, and calcined at 600°C for 6 hours to obtain an oxide precursor Ni with a median particle size of 4 μm. 0.4 Fe 0.2 Mn 0.4 O 1.5 .
[0174] The above oxide precursors and Na 2 CO 3 The mixture is sintered in an atmosphere furnace and compressed air is introduced at a heating rate of 3°C / min and kept at 930°C for 18 hours. After it is naturally cooled, the obtained block material is crushed and sieved by a jet mill to obtain an O3 phase layered oxide matrix material.
[0175] (2) Coating modification:
[0176] According to the coating ratio, weigh Al 2 O 3 , CaO, and MgO, disperse them in water, and add dispersing additive PVA, ultrasonically disperse the mixture for 60 minutes, then filter and wash, and place it in a 120°C forced air drying oven for drying to obtain a composite material.
[0177] The O3 phase layered oxide matrix material and the composite material were weighed respectively according to the above coating ratio, mixed evenly using a high-speed mixer, and put into a sagger, sintered at 850°C for 15h in a compressed air atmosphere, and then naturally cooled to room temperature to obtain a high-voltage positive electrode material.
[0178] Example 10
[0179] The composition of the high voltage positive electrode material provided in this embodiment is the same as that in embodiment 4, but the preparation method is different. The difference in the preparation method is as follows: the coating modification method in step (2) is as follows: weigh the O3 phase layered oxide matrix material, B 2 O 3 and ZrO 2 , use a high-speed mixer to mix evenly, put it into a sagger, sinter it at 870°C for 10 hours in a compressed air atmosphere, and then cool it naturally to room temperature to obtain a high-voltage positive electrode material (that is, no wet mixing is performed in advance).
[0180] Embodiment 11
[0181] The composition of the high voltage positive electrode material provided in this embodiment is the same as that in embodiment 5, but the preparation method is different. The difference in the preparation method is as follows: the coating modification method in step (2) is as follows: weigh the O3 phase layered oxide matrix material, B 2 O 3 and CoO, are mixed evenly using a high-speed mixer, and are placed in a sagger, sintered at 830° C. for 12 h in a compressed air atmosphere, and then naturally cooled to room temperature to obtain a high-voltage positive electrode material (i.e., without prior wet mixing).
[0182] Example 12
[0183] The composition of the high voltage positive electrode material provided in this embodiment is the same as that in embodiment 9, but the preparation method is different. The difference in the preparation method is as follows: the coating modification method in step (2) is as follows: weigh the O3 phase layered oxide matrix material, Al2O ... 2 O 3 , CaO and MgO are mixed evenly using a high-speed mixer, and placed in a sagger, sintered at 850°C for 15 hours in a compressed air atmosphere, and then naturally cooled to room temperature to obtain a high-voltage positive electrode material (i.e., no wet mixing is performed in advance).
[0184] Example 13
[0185] The high voltage positive electrode material and the preparation method thereof provided in this embodiment are basically the same as those in embodiment 4, except that the O3 phase layered oxide matrix material is Na 1.0 Zn 0.05 Ni 0.45 Mn0.45 Ce 0.05 O 2 , no CuSO was added during the preparation process 4 6H 2 O and TiCl 4 (N liquid), but NiSO 4 6H 2 O、ZnSO 4 7H 2 O、CeSO 4 、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 of saline solution.
[0186] Embodiment 14
[0187] The high voltage positive electrode material and the preparation method thereof provided in this embodiment are basically the same as those in embodiment 4, except that the O3 phase layered oxide matrix material is Na 0.9 Ca 0.05 Ni 0.5 Mn 0.4 Mo 0.05 O 2 During the preparation process, NiSO 4 6H 2 O、Na 2 MoO 4 、MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 of salt solution, while transferring the stoichiometric ratio of CaC 2 O 4 , and disperse it in dilute hydrochloric acid, recorded as N solution.
[0188] Embodiment 15
[0189] The high voltage positive electrode material and the preparation method thereof provided in this embodiment are basically the same as those in embodiment 4, except that the O3 phase layered oxide matrix material is Na 1.02 Mg 0.1 Ni 0.4 Mn 0.4 Zr 0.1 O 2 , no CuSO was added during the preparation process 4 6H 2 O and TiCl 4 (N liquid), but NiSO 4 6H 2O、MgSO 4 7H 2 O、ZrSO 4 and MnSO 4 ·H 2 O was mixed and dissolved according to the target chemical formula ratio, and the solvent was pure water to obtain a total molar concentration of 2 mol·L -1 of saline solution.
[0190] Example 16
[0191] The high voltage positive electrode material and the preparation method thereof provided in this embodiment are basically the same as those in embodiment 4, except that the coating layer is La 2 O 3 SnO 2 and CeO 2 The mass of the coating layer is 5% of the mass of the O3 phase layered oxide matrix material, wherein La 2 O 3 SnO 2 and CeO 2 The mass fractions of La were 2%, 2% and 1% respectively. 2 O 3 SnO 2 and CeO 2 Dosage.
[0192] Embodiment 17
[0193] The high voltage positive electrode material and the preparation method thereof provided in this embodiment are basically the same as those in embodiment 4, except that the coating layer is MoO 3 , WO 3 and Y 2 O 3 The mass of the coating layer is 8% of the mass of the O3 phase layered oxide matrix material, wherein MoO 3 , WO 3 and Y 2 O 3 The mass fractions of MoO are 5%, 2% and 1% respectively. 3 , WO 3 and Y 2 O 3 Dosage.
[0194] Comparative Example 1
[0195] The positive electrode material provided in this comparative example is the O3-phase layered oxide matrix material Na prepared in step (1) of Example 1. 0.9 Cu 0.1 Ni 0.4 Mn 0.4 Ti0.1 O 2 (ie no coating).
[0196] Comparative Example 2
[0197] The positive electrode material provided in this comparative example is the O3-phase layered oxide matrix material Na prepared in step (1) of Example 6. 0.95 Ni 0.4 Fe 0.2 Mn 0.4 O 2 (ie no coating).
[0198] Comparative Example 3
[0199] The positive electrode material and preparation method provided in this comparative example are basically the same as those in Example 1, except that the O3 phase layered oxide matrix material is Na 1.0 Ni 0.5 Mn 0.5 O 2 , CuSO was not added in step (1) 4 6H 2 O and TiCl 4 .
[0200] Comparative Example 4
[0201] The positive electrode material and preparation method provided in this comparative example are basically the same as those in Example 1, except that the O3 phase layered oxide matrix material is Na 0.9 Cu 0.3 Ni 0.4 Mn 0.2 Ti 0.1 O 2 , the molar ratio of each element is adaptively adjusted during the preparation process.
[0202] Experimental example
[0203] The high voltage positive electrode materials prepared in each embodiment and the positive electrode materials prepared in each comparative example were respectively used as positive electrode active materials and assembled into a sodium ion secondary battery according to the following method: (1) Preparation of positive electrode sheet: Weigh each raw material according to the mass ratio of positive electrode active material, SP and PVDF of 90:5:5, grind and mix the positive electrode active material and SP, then drop a glue solution containing PVDF therein to obtain a mixed solution, centrifuge and degas the mixed solution, then coat it on an aluminum foil current collector, and apply it with a scraper with a thickness of 150 μm, dry it at 70°C and cut it into pieces to obtain a diameter of The cathode electrode is 12 mm thick. The entire process of preparing the cathode electrode is carried out in a dry room. (2) Button cell assembly: Sodium metal sheet is used as the counter electrode, glass fiber is used as the separator, and NaPF with a sodium ion concentration of 1 mol / L is used. 6A solution (the solvent is a mixture of EC and DMC, with a volume ratio of EC / DMC=1:1) was used as the electrolyte to assemble 2032 button cells in an Ar atmosphere protection glove box, wherein the surfaces of the button cell shell and its components used for assembly were aluminum-plated.
[0204] According to the following method, the electrochemical performance of each button cell was tested respectively: in Examples 1-5, 10-11, 13-17, Comparative Example 1 and Comparative Example 3-4, the charge and discharge curve test method is as follows: the 2032 button cell is placed at a temperature of 25°C, and tested using a Xinwei button test cabinet, with a test voltage of 2-4.3V, and charged and discharged at 0.1C and 0.5C rates in turn, for three cycles, and then 100 cycles at 1C rate, and it needs to be rested for more than 2 hours before testing. The test results are shown in Table 1.
[0205] In Example 6-Example 9, Example 12 and Comparative Example 2, the charge and discharge curve test method is as follows: Place the 2032 button cell at a temperature of 25°C, use the Xinwei button cell test cabinet for testing, the test voltage is 2-4.25V, and charge and discharge at 0.1C and 0.5C rates in turn for three cycles, then perform a 100-cycle test at a 1C rate, and let it rest for more than 2 hours before testing. The test results are shown in Table 1.
[0206] Table 1 First charge and discharge capacity and cycle performance results
[0207]
[0208]
[0209] It can be seen from Table 1 that the high voltage positive electrode material provided by the present invention can operate at a high voltage greater than 4V or even 4.3V.
[0210] Specifically, compared with Comparative Examples 1 and 2, the cycle performance of the batteries assembled with the positive electrode materials having the coating layer in Examples 1 and 6 is significantly improved. This is because the coating layer of the positive electrode material acts as a physical barrier, which can effectively inhibit the side reaction between the positive electrode material and the electrolyte, and reduce the dissolution of the transition metal in the positive electrode material. The two-phase heterojunction structure formed at the interface between the coating material and the base material can improve the electronic and ionic conductivity, promote the interfacial ion charge transfer, stabilize the structure to a certain extent, and improve the cycle stability of the material.
[0211] Furthermore, compared with Example 1, the matrix material used in Comparative Example 3 is not doped with Cu and Ti, resulting in a decrease in cycle capacity of more than 10%. This is because the addition of Cu and Ti enhances the TM-O bonding, stabilizes the crystal structure, and reduces the probability of battery failure due to TM dissolution in the positive electrode material during the cycle.
[0212] Compared with Example 1, the amount of Cu doped in the matrix material used in Comparative Example 4 is too large, resulting in a significant decrease in cycle capacity and capacity retention. This is attributed to the excessive addition of Cu, which occupies the lattice site where Ni is located, causing Ni to segregate to form rock salt phases such as NiO. First, it leads to an increase in charge transfer impedance. Second, due to the inconsistency between the layered oxygen structure and the contraction and expansion of the rock salt phase during the charge and discharge process of the material, microcracks are generated, which leads to a comprehensive deterioration in battery performance.
[0213] In addition, compared with Examples 10, 11 and 12 of simple dry mixing, Examples 4, 5 and 9 respectively use wet mixing to obtain composite materials and then coat them during coating modification, and their cycle performance is further improved. This is because the elements of the composite materials obtained by wet pretreatment are more evenly distributed, and the coating elements on the surface of the matrix material are evenly distributed, which can form a uniform multiphase heterojunction structure. Through the multiphase synergistic effect, it is more conducive to the transmission of electrons, improves the kinetics of sodium ion reactions, and significantly improves the cycle stability of the positive electrode material.
[0214] In summary, the high voltage positive electrode material provided by the present invention has a reversible phase change at a high voltage greater than 4V, can work at a high voltage greater than 4V or even ≥4.3V, and has excellent cycle performance. At the same time, by pre-wetting the coating material to obtain a composite coating material with uniform element distribution, and then compounding it with the base material through heat treatment, the cycle performance can be further improved.
[0215] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A high voltage positive electrode material, characterized in that: It comprises an O3 phase layered oxide matrix material and a coating layer coated on the surface of the O3 phase layered oxide matrix material; Wherein, the chemical formula of the O3 phase layered oxide matrix material is Na a Ni x A y Mn p G q O2, wherein A includes +2 and / or +3 valence metal elements, G includes +4 valence metal elements, 0.8≤a≤1.05, 0.3≤x≤0.5, 0≤y≤0.2, 0.3≤p≤0.5, 0≤q≤0.2, x+y+p+q=1, 2(x+y)+4(p+q)≤3, and y and q are not 0 at the same time; The modifying element in the coating layer includes at least one of Al, B, Ca, Co, Ce, La, Mg, Mo, Nb, Sr, Sn, W, Y, Zr, Zn, Bi and Ti.
2. The high voltage positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The +2 valence metal element in A includes at least one of Ca, Zn, Cu and Mg; (2) the +3 valence metal element in A includes at least one of Fe and Co; (3) The G includes at least one of Ti, Ce, Zr and Mo.
3. The high voltage positive electrode material according to claim 1, characterized in that: The mass of the coating layer accounts for 0.3% to 10% of the mass of the O3 phase layered oxide matrix material; And / or, the coating layer includes an oxide of a modifying element.
4. The method for preparing a high voltage positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: (a), mixing a mixed aqueous solution containing a nickel source, a manganese source, a dispersant and an additive with a precipitant solution and performing a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor; or, mixing a mixed aqueous solution containing a nickel source, a manganese source and a dispersant, an organic solution or an acid solution containing an additive, and a precipitant solution, and performing a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor; or, mixing a mixed aqueous solution containing a nickel source, a manganese source, a dispersant and an additive, an organic solution or an acid solution containing an additive, and a precipitant solution, and performing a coprecipitation reaction to obtain a hydroxide precursor and / or a carbonate precursor; wherein the additive comprises an A-containing compound and / or a G-containing compound, A comprises a +2 and / or +3 valence metal element, and G comprises a +4 valence metal element; optionally, calcining the hydroxide precursor and / or the carbonate precursor to obtain an oxide precursor; (b) mixing at least one of the hydroxide precursor, the carbonate precursor and the oxide precursor with a sodium source, and then sintering to obtain an O3 phase layered oxide matrix material; (c) When one coating agent is used, the O3 phase layered oxide matrix material is mixed with the coating agent and then subjected to heat treatment to obtain the high voltage positive electrode material; or, when at least two coating agents are used, each of the coating agents, dispersing additives and water are first mixed and ultrasonicated, and then the solid-liquid separation and drying are performed to obtain a composite material, and then the composite material is mixed with the O3 phase layered oxide matrix material and subjected to heat treatment to obtain the high voltage positive electrode material; wherein the coating agent includes a compound containing a modifying element, and the modifying element includes at least one of Al, B, Ca, Co, Ce, La, Mg, Mo, Nb, Sr, Sn, W, Y, Zr, Zn, Bi and Ti.
5. The method for preparing a high voltage positive electrode material according to claim 4, characterized in that: In step (a), at least one of the following conditions is met: (1) The dispersant comprises at least one of soluble starch, polyvinyl pyrrolidone, sodium dodecyl sulfate and polyethylene glycol; (2) the organic solvent in the organic solution containing the additive comprises at least one of ethanol, dichloromethane and anhydrous tetrahydrofuran; (3) the A-containing compound includes at least one of an A-containing nitrate, an A-containing sulfate, an A-containing chloride, and an A-containing acetate; (4) the G-containing compound includes at least one of a G-containing nitrate, a G-containing sulfate, a G-containing chloride and a G-containing acetate; (5) The +2 valence metal element in A includes at least one of Ca, Zn, Cu and Mg, and the +3 valence metal element in A includes at least one of Fe and Co; (6) G includes at least one of Ti, Ce, Zr and Mo; (7) The precipitant solution includes at least one of a sodium carbonate solution, a sodium hydroxide solution and an ammonia solution.
6. The method for preparing a high voltage positive electrode material according to claim 4, characterized in that: In step (a), at least one of the following conditions is met: (1) The pH of the coprecipitation reaction is 7 to 13; (2) The calcination temperature is 400-700° C. and the holding time is 6-12 hours; (3) The calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
7. The method for preparing a high voltage positive electrode material according to claim 4, characterized in that: In step (b), at least one of the following conditions is met: (1) The sodium source includes sodium carbonate and / or sodium hydroxide; (2) The sintering temperature is 850-1050° C. and the holding time is 12-24 hours; (3) The sintering comprises: firstly keeping the temperature at 400-600°C for 3-6 hours, and then keeping the temperature at 850-1050°C for 14-18 hours; (4) The sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
8. The method for preparing a high voltage positive electrode material according to claim 4, characterized in that: In step (c), at least one of the following conditions is met: (1) The total mass of each of the coating agents accounts for 0.3% to 10% of the mass of the O3 phase layered oxide matrix material; (2) the dispersing additive comprises at least one of sodium polyacrylate, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium lauryl sulfate, polyvinyl alcohol and polyoxyethylene; (3) The ultrasound duration is 30 to 60 minutes; (4) The heat treatment temperature is 500 to 950° C. and the holding time is 10 to 16 hours; (5) The atmosphere of the heat treatment includes air atmosphere and / or oxygen atmosphere; (6) The compound containing the modifying element includes at least one of carbonate, bicarbonate, nitrate, acetate, oxalate, hydroxide, sulfate, chloride and oxide containing the modifying element.
9. A positive electrode sheet, characterized in that: The invention comprises the high voltage positive electrode material as claimed in any one of claims 1 to 3.
10. A sodium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.
Citation Information
Cited By
Composite phosphate coated high-voltage sodium-electrode layered oxide positive electrode material and preparation method thereof
CN121076112A
Composite phosphate-coated high-voltage sodium electric layered oxide positive electrode material and preparation method
CN121076112B
